Health Risk of Ingested Heavy Metals in Fluidized Canned Milks: Are We Drinking Heavy Metals? - Victor Eshu Okpashi (Journal of Food Quality)
This study examined the heavy metal level of canned milk consumed in Calabar, Cross River State, as well as the health risks linked to it. Peak Milk, Three Crown, Coast, Nunu, Cowbell, and Olympic milk types were chosen for research. During the digestion of samples, 0.5 mol of nitric acid was added to the sample and heated. The heated liquid was slowly heated with 2.5 mL of 70% HClO4 until a dense white vapor was formed. After cooling the mixture, 10 mL of deionized water was added and the solution was boiled to expel the fumes. The heavy metals were screened using an atomic absorption spectrophotometer. All milk samples contained eight heavy metals: iron (Fe), copper (Cu), zinc (Zn), arsenic (As), lead (Pb), cadmium (Cd), manganese (Mn), and nickel (Ni). Peak Milk and Nunu both had Cd. Nickel was found in various quantities in Coast, Cowbell, Nunu, and Olympic. Coast, Nunu, and Cowbell samples all contained Mn. Nunu and Cowbell both tested positive for lead. Peak Milk did not contain copper (Cu). Standard models for daily consumption of different heavy metals, such as Pb in Nunu (3.7E − 03) and Cowbell (−1.8E − 03), were used to construct the health risk evaluations. Peak Milk, Three Crown, and Nunu had daily Cd intakes of (4.5E − 06), (2.2E − 05), and (4.5E − 06), respectively. Coast (3.2E − 02), Nunu (5.1E − 02), Cowbell (1.9E − 02), and Olympic (3.8E − 02) have different daily Ni intakes. Peak Milk (1.1E − 01), Three Crown (2.2E − 01), Coast (1.6E − 01), Nunu (7.1E − 01), Cowbell (1.4E − 01), and Olympic (1.1E − 01) have different daily intakes of Ar. Peak (6.0E − 04), Three Crown (8.0E − 04), Coast (6.0E − 04), Nunu (7.0E − 04), Cowbell (8.0E − 04), and Olympic (6.0E − 04) had different daily Zn intakes. Daily Fe intakes of Peak Milk was (1.6E − 01), Three Crown was (1.6E − 01), Coast was (1.4E − 01), Nunu was (1.4E − 01), Cowbell was (2.4E − 01), and Olympic was (1.8E − 01). Cu intakes per day for Three Crown, Coast, Nunu, Cowbell, and Olympic were (6.0E − 03), (4.0E − 03), (2.0E − 03), (2.0E − 03), and (4.0E − 03), respectively. Coast, Nunu, and Cowbell had daily Mn intakes of (2.0E − 04), respectively. The total hazard index (THI) and the target hazard quotient (THQ) were also calculated. Peak Milk (1.7E − 01), Three Crown (3.4E − 01), Coast (2.8E − 01), Nunu (1.9E − 01), Cowbell (2.4E − 01), and Olympic (2.3E − 01) induced cancer risks, accordingly. According to the findings, the risk of drinking milk is relatively considerable when compared to the acceptable limit.